Short-term and long-term effects of exposure to PM10 - Narges Seihei; Majid Farhadi; Afshin Takdastan; Parisa Asban; Fatemeh Kiani; Mohammad Javad Mohammadi (Elsevier, 2024)
Introduction: A dust storm is a harmful event in the environment and human health resulting from certain chemicals in the air that transcend predefined levels. Developing countries, such as Iran, suffer from this basic threat (dust particles) to health. The purpose of the research was to evaluate the effects of PM10 particulate matter on mortality related to cardiovascular diseases (CVD) in the year 2022-2023 in Andimeshk City, with the AirQ + programmed. Material and method: The recommended approach for evaluating effects on health, as recognized by the world health organization (WHO), uses the Air Quality Health Impact Assessment Software (Air Q 2.2.3). The polluted air information required for model runs was obtained from the Environmental Department of Khuzestan. The Khuzestan Meteorological Organization gave information on the levels of particulate matter for both dusty and non-dusty days. The mortality numbers came from the Iranian Statistics Centre and the Health Ministry. The data was collected in a volumetric manner for the year 2022-2023. Result: The lowest PM10 concentration reported in a year in Andimeshk city belonged to January 9 (14.19 μg/m3), while the most polluted day of the year was November 6 (5634.61 μg/m3). The total monthly concentration of PM10 for April, May, June, July, August, September, October, November, December, January, and February respectively, 2917.9, 3227.82, 3175.89, 2966.24, 3520.46, 3393.1, 4671.07, 13121.26, 3042.63, 1851.67, 2627.52, and 6758.12 μg/m3. Conclusion: The results of this study showed that the studied area is a polluted city in terms of the concentration of dust particles. So, during a year, only 8 days, PM10 concentration did not exceed the standard. One of the main reasons for air pollution in Andimshek city is the neighborhood of Khuzestan province with Iraq and Saudi Arabia, which have dry areas and dust storms.